2009
DOI: 10.3390/ijerph6031124
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of a Clinically Relevant Dose of Hydroxyurea Used for the Treatment of Sickle Cell Disease on Male Fertility Endpoints

Abstract: Abstract:Two experiments were conducted to determine: 1) whether the adult male transgenic sickle cell mouse (Tg58 × Tg98; TSCM), exhibits the patterns of reproductive endpoints (hypogonadism) characteristic of men with sickle cell disease (SCD) and 2) whether hydroxyurea (HU) exacerbates this condition. In Experiment 1, blood samples were collected from adult age-matched TSCM and ICR mice (ICRM) (N = 10/group) for plasma testosterone measurements. Subsequently, mice were sacrificed, testes excised and weighed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 59 publications
3
44
0
Order By: Relevance
“…They found that 91% of men with SCD had at least one parameter that was abnormal (lower than 5th percentile) [127]. Additionally, experiments in transgenic sickle cell mice suggest that hydroxyurea therapy decreases spermatogenesis and causes testicular atrophy exacerbating SCD-related hypogonadism [128]. Limited observational studies have reported similar findings in men with SCD [127]; however, large-scale studies are lacking.…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…They found that 91% of men with SCD had at least one parameter that was abnormal (lower than 5th percentile) [127]. Additionally, experiments in transgenic sickle cell mice suggest that hydroxyurea therapy decreases spermatogenesis and causes testicular atrophy exacerbating SCD-related hypogonadism [128]. Limited observational studies have reported similar findings in men with SCD [127]; however, large-scale studies are lacking.…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…The benefits of HU in sickle cell disease were evaluated in a number of studies, some of which facilitate the wider use of HU, and others highlighted some of its adverse effects. (20)(21)(22)(23)(24)(25) Although the condition is widely prevalent in Saudi Arabia, research around SCA management and the use of HU remains limited. In this study, we explore the perception of SCA patients admitted with VOC on the use of HU, and any accompanying clinical or biomedical changes.…”
Section: Int J Adv Res 5(2) 2345-2350mentioning
confidence: 99%
“…This dose was increased at a rate of (5) mg/kg/week, as long as the hematologic indices remained within acceptable range, and given that the patient showed no evidence of adverse effects. The maximum dose of HU reached per patient was between (25) to (35) mg/kg/day. All patients remained on HU for six to nine months, and was only discontinued when adverse events were reported, the latter included symptoms such as hair loss, gastrointestinal upset and rash, or disturbance of their blood indices; Hb drop to (6) g/dl, platelet count <80,000 or a neutrophil count <2,500.…”
Section: Management Protocol:-mentioning
confidence: 99%
“…Regional clustering has been described for Chuvash polycythemia, which is endemic in the Chuvash Republic, part of the Russian Federation, 18 and for the MPL-S505N mutation, which was present in four out of five Italian families with thrombocytosis studied. 19 The fact that all of these families originated from the region around Rome suggests…”
Section: Jak2-v617fmentioning
confidence: 99%
“…18 Since then, a study in male transgenic sickle mice revealed 69% and 95% decreases in sperm density and motility, respectively. 19 A comparison of semen before and after cessation of treatment in 44 SCD patients showed that observed alterations of semen due to SCD seemed to be exacerbated by hydroxyurea treatment. 20 The development of new technologies is lengthening the life of patients with SCD and improving its quality.…”
mentioning
confidence: 99%